(untitled) (TAMADDUN NURI JURNALI, 2024)
The article is devoted to the problem of studying the lexical and semantic group of verbs. Various classifications of lexical and semantic groups of verbs of the Russian language, as well as their features, are considered. The article presents various research approaches to the study of this field of linguistics by famous linguists: L.M. Vasilyeva, Yu.D. Apresyan, A.A., Kuznetsova, N.Yu. Shvedova N.Yu., etc.